Magic prose of Vasilij Belov - Zdeňka Matyušová (Opera slavica, 2014)
Vasiliy Belov (1932–2012) belongs to the noticeable representatives of the so called Russian Rural Prose. He started his literary activities as a poet and his strong poetic feelings found their expression in lyrically full prose. His work is constantly and firmly linked with the Northern Vologdian Village and the poet himself is closely connected to natural environment, which is expressed in his books fully and accurately. Belov's life itself is also reflected in his whole work. The world of his prose is highly ethical and moral, poetic and delightful. The value of his works lies in their strong emotional profuseness, in the great artistic strength and in their extremely high moral potential. Vasiliy Belov undoubtedly ranges with the most significant contemporary Russian prose writers.